Ontological (In)Security and the Kurdish Issue in Turkey: The Use of Security Discourse (1925‒1984) - Balaban, Gökçe (Poligrafi, 2021)
How could one account for the discourse of security used by the Turkish state considering the Kurdish issue before 1984, when the terrorist attacks of the Partiya Karkaren Kurdistani (PKK) had not yet started, and hence there was no physical security threat against the state? This article aims to answer this question from the perspective of ontological (in)security. Based on Critical Discourse Analysis of state discourse, the article argues that the political, social and cultural traits of Kurdish identity created uncertainty in the Turkish self after the Sheikh Said rebellion in 1925. Tribal/religious structures that were influential among Kurds and the expression of Kurdishness as a distinct identity disrupted the autobiographical narratives about Turkishness, hence generating ontological insecurity for the Turkish state. To overcome this problem, the state relied on security discourse and securitized the traits of Kurdish identity, by which it felt threatened. As a result of this securitization, the state was able to legitimize the extraordinary measures taken against Kurds, such as forced resettlements. Securitization, in this sense, regenerated ontological security for the state, because the extraordinary measures served to suppress the Kurdish identity that threatened the certainty and continuity of the Turkish self.